MALFUNGSI HAN DAN UPAYA MELAKUKAN REKONSTRUKSI SISTEM HUKUM YANG ADA MENUJU HUKUM YANG MELAYANI - Jawade Hafidz (Jurnal Hukum, 2012)
The republic of Indonesian is a law country with welfare state concept. Consequently, each activity should be oriented around the goals based on the law that organize state activities, government, and society. The State is required to play a role and to interfere on its socety life in order to achieve prosperity. One of the important role is state administration to serve the society. In recent time, state administrative law plays a large role, because the state grants the authority to government in organizing society’s concerns and welfare, which mean the state to be functionsto serve socety’s needs.Keywords: Law, Serve, Society